Effect of vermicompost tea on seed germination of Green Romaine (Lactuca sativa L. var. Jericho) and Green Batavia (Lactuca sativa L.var Concept) Lettuce - vithirak, Huy; Boonthai Iwai, Chuleemas (วารสารแก่นเกษตร, 2019)
Vermiculture is a technology which uses earthworm and microorganism to convert solid waste to become organic fertilizer. It can be collected vermicompost tea during decomposition of vermicompost. Vermicompost tea is liquid biofertilizer which can use to boot up plant nutrients and plant productions. Vermicompost tea was normally diluted being apply to plant and avoid plant damage. The objective of this study was to investigate and to find a suitable concentration of vermicompost tea for growing seed of Green Romaine (Lactuca sativa L. var. Jericho) and Green Batavia (Lactuca sativa L.var Concept) Lettuce. The experiment was arranged in a Complete Randomized Design with 3 replications in the petri dish. Vermicompost tea concentration was diluted to 0, 25, 50, 75, and 100% and applies to lettuce seeds both varieties. 13 days of the experiment, seed germination percentage, shoot length, root length, seed vigor index, fresh weight, and dry weight were collected. The results showed that 25 and 50 % of vermicompost tea were not significantly increase seed germination of Green Romaine and Batavia compared to control (p>0.05) but (75 and 100%) were significantly decrease the seed germination than the control. Nevertheless, 50 % vermicompost tea was significant increase in shoot length, root length, seed vigor index, fresh weight and dry weight of both lettuce varieties compared to other treatments (p>0.05). Therefore, 50% vermicompost tea could be used to improve seed growth of both lettuce varieties.